Peran Penyuluh Pertanian Lapangan dalam Pengembangan Subak Selat sebagai Wahana Belajar Petani di Kecamatan Selat Kabupaten Karangasem (Jurnal Agribisnis dan Agrowisata, 2025)
Extension Worker in the Development of Subak Selat as a Farmers Learning Forum in Selat District, Karangasem Regency.  Extension worker are people who are in charge of being a liaison between the government and farmers and with researchers who aim to convey all information to improve farmers' abilities in terms of education, skills and insight so they can make the right decisions. The purpose of this research is to find out the role of Extension worker as communicators, mentors, facilitators in the development of Subak Straits as a vehicle for learning for farmers in Selat District, Karangasem Regency. The sample in this study was 40 people, the data collection method used a survey method, while the data analysis in this study used descriptive qualitative analysis. The results of this study indicate that the role of Extension worker as a communicator, mentor, facilitator in the development of Subak Selat, Selat District, Karangasem Regency is classified as good, the role of Extension worker in developing Subak Selat as a medium for exchanging information, increasing production, media innovation is classified as good, because the information conveyed to farmers is very actual, easy, quality, and has been able to become a medium for spreading innovation so that increased production is achieved.